Behavioral barriers of tuberculosis notification in private health sector: policy implication and practice. Issue 4 (17th September 2020) - Ahmadi, Ayat; Doshmangir, Leila; Gordeev, Vladimir Sergeevich; Yazdizadeh, Bahareh; Majdzadeh, Reza
Abstract : Purpose: Underreporting of new tuberculosis (TB) cases is one of the main problems in TB control, particularly in countries with high incidence and dominating role of a private sector in TB cases diagnosing. The purpose of this paper was to explore behavioral determinants of underreporting of new TB cases among private sector physicians in Iran. Design/methodology/approach: The authors conducted a population-based, cross-sectional study of physicians working in private clinics. The data collection tool was designed using the theory of planned behavior (TPB). The authors used structural equation models with maximum likelihood estimation to examine attitude toward the notification behavior. Findings: Of 519 physicians, 433 physicians completed the questionnaire. Attitude toward notification had the highest score (mean score = 87.65; sd = 6.79; range: 0–100). The effect of perceived behavioral controls on the notification behavior (( β ^ ) = 0.13; CI: 0.01–0.25) was stronger than the total effect of attitude (( β ^ ) = 0.06; CI: 0.00–0.12) and subjective norms (( β ^ ) = 0.01; CI: −0.00–0.03) on the behavior. However, the attitude was the main predictor of intention and justified 46% of the intention variance. Intention had a significant effect on the behavior (( ß ^) = 0.09; CI: 0.1–0.16). Practical implications: Considering stronger effect of perceived behavioral control on the behavior, interventions aiming at facilitating notification process would be more effective than those aiming at changing the attitude or enhancing intention among physicians. Originality/value: To the best of our knowledge, no other study previously explored determinants of underreporting from the behavioral and cognitive perspective. Specifically, the authors explored the role of the TPB constructs in predicting intention to notify new TB cases.